(untitled) (مجلة إحالات, 2026)
This article sets out to present some sociolinguistic factors impacting the teaching-learning of French in scientific fields in Morocco. Thus, we will question, upstream, by means of a field survey which is directed towards the students of the national school of applied sciences of kénitra and those registered in Master at the faculty of sciences located in the same city, the sociocognitive parameters of the students. We will then uncover the results obtained which will give us, downstream, indicators on the linguistic and communication skills that students must acquire in order to better understand the teaching-learning process in question.